SERVICE SECTOR'S CONTRIBUTION TO THE ECONOMIC GROWTH OF CHINA: CASE OF REAL ESTATE AND HOTEL & CATERING - -Martin, X., Sala-I (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
This study explores the impact of real estate and hotel & catering sub-sectors on China's economic growth. Using ARDL methodology, data covering the period 1990-2018 was analyzed to establish a long-run and short-run relationship between economic growth and the two sub-sectors. The study finds that both sub-sectors have significant positive impacts on China's economic growth, with the service sector positively contributing to the growth of the Chinese economy. Additionally, the article discusses China's transition from a reliance on capital accumulation to policies and reforms, emphasizing the need for further technological progress and innovation in high value-added industries. The study highlights the importance of developing the service sector to increase its contribution to economic growth in China. The authors recommend the establishment of policies and regulations to decrease inequalities in development among different regions of China and to promote growth in other sub-sectors of the service industry. Overall, the study provides policymakers with empirical evidence to support their efforts to sustain productivity and growth in China.